Transient Stability Enhancement Using Phasor Model of Superconducting Magnetic Energy Storage - Mohamed Bey; Mohamed Moudjahed (Bulletin of Electrical Engineering and Informatics, 2016)
Superconducting Magnetic Energy Storage (SMES) is one of most important device attracting researchers for enhancing the transient stability of power systems. To facilitate the use of this device in different simulations and studied, a phasor model is established and used to analyse the impact of this device using matlab/Simulink software. The phasor model has enough advantages like using the SMES without need detailed model that contains the electronic power converter and therefore minimize the simulation time. The Western Systems Council Coordinating (WSCC) 3 machine-9 bus system is taken as a power system test. Simulation results show that the phasor model of SMES unit is very effective to study their impact for enhancing the transient stability in large scale time.